Educational Perception in Urban and Rural Communities: A Qualitative Study - Mochamad Iqbal At-tamimy At-tamimy; Michael Jhon Aderson Eloy (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Education plays a crucial role in shaping the future of individuals and communities. However, the perception of education can vary significantly between urban and rural areas due to differences in access to resources, infrastructure, and cultural norms. This study aims to explore the perceptions of education in both urban and rural communities in Indonesia. Using a qualitative approach, data were collected through in-depth interviews with 30 respondents, including students, teachers, parents, and educational leaders. The findings indicate that urban communities generally have a more positive perception of education, often viewing it as a pathway to better career opportunities and economic stability. In contrast, rural communities tend to perceive education as valuable but face significant barriers, including limited access to quality educational facilities, inadequate teaching resources, and economic constraints. These challenges often lead to lower educational aspirations and higher dropout rates in rural areas. The study highlights the need for targeted educational interventions and policies that address these disparities, ensuring equal educational opportunities for all students, regardless of their geographical location.